Command Responsibility of Autonomous Weapons Systems under International Humanitarian Law - Yordan Gunawan; Mohammad Haris Aulawi; Andi Rizal Ramadhan (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractWar and Technological development have been linked for centuries. States and military leaders have been searching for weapon systems that will minimize the risk for the soldier, as technology-enabled the destruction of combatants and non-combatants at levels not seen previously in human history. Autonomous Weapon Systems are not specifically regulated by IHL treaties. On the use of Autonomous Weapons Systems, there are three main principles that must be considered, namely principle of Distinction, Proportionality and Unnecessary Suffering. Autonomous weapon systems may provide a military advantage because those systems are able to operate free of human emotions and bias which cloud judgement. In addition, these weapon systems can operate free from the needs for self-preservation and are able to make decisions a lot quicker. Therefore, it is important to examine who, in this case, the commander can be held responsible when an Autonomous Weapon System will commit a crime.Keywords: Command Responsibility, Autonomous Weapons Systems, International Humanitarian Law AbstrakPerang dan perkembangan Teknologi telah dikaitkan selama berabad-abad. Para pemimpin negara dan militer telah mencari sistem senjata yang akan meminimalkan risiko bagi prajurit itu, karena teknologi memungkinkan penghancuran para pejuang dan non-pejuang pada tingkat yang tidak terlihat sebelumnya dalam sejarah manusia. Sistem Senjata Otonom tidak secara spesifik diatur oleh perjanjian IHL. Pada penggunaan Sistem Senjata Otonom, ada tiga prinsip utama yang harus diperhatikan, yaitu prinsip Perbedaan, Proportionalitas, dan Penderitaan yang Tidak Perlu. Sistem senjata otonom dapat memberikan keuntungan militer karena sistem tersebut dapat beroperasi bebas dari emosi manusia dan bias yang menghakimi. Selain itu, sistem senjata ini dapat beroperasi bebas dari kebutuhan untuk pelestarian diri dan mampu membuat keputusan lebih cepat. Oleh karena itu, penting untuk memeriksa siapa, dalam hal ini, komandan dapat bertanggung jawab ketika Sistem Senjata Otonom akan melakukan kejahatan.Kata kunci: Tanggung Jawab Komando, Sistem Senjata Otonom, Hukum Humaniter Internasional АннотацияВойна и развитие технологий были связаны на протяжении веков. Государственные и военные лидеры искали системы вооружений, которые минимизируют риски для солдат, потому что технология позволяет уничтожать боевиков и не боeвиков на уровне, невиданном ранее в истории человечества. Автономный Комплекс Вооружения конкретно не регулируется соглашением о МГП (Международное Гуманитарное Право). При использовании Автономного Комплекса Вооружения необходимо учитывать три основных принципа, а именно: принцип различия, пропорциональность и потери среди мирного населения. Автономный Комплекс Вооружения может обеспечить военные преимущества, поскольку он может функционировать без человеческих эмоций и субъективных предубеждений. Кроме того, эта система вооружения может работать без необходимости самосохранения и может принимать решения быстрее. Поэтому важно выяснить, кто, в этом случае, командир, может нести ответственность, когда Автономный Комплекс Вооружения совершит преступление. Ключевые слова: Командная ответственность, Автономный Комплекс Вооружения, Международное Гуманитарное Право